Evaluating Library Escape: A Prototype Information Literacy Game - Guo, Yan Ru (2016)
Digital game-based learning has grown rapidly in recent years, including in information literacy (IL) education. However, many efforts have failed because users are not involved in the design process. The present study adopts a user-centered design approach to evaluate an educational IL game prototype, with data analyzed based on Pedagogical Playability Heuristics.